Analisis Faktor-Faktor Psikologis Yang Mempengaruhi Kemampuan Afektif Anak Di Sekolah Dasar - Sr. Sipayung. R; Siahaan. S; Sihombing F.Y.S; Lubis. S; Sinaga. K; Turnip. E; Nahampun. D (Jurnal Kabar Masyarakat, 2024)
This material explores the role of education in primary schools as an effort to enlighten and shape the character of students. It focuses on students aged 6-12, emphasizing mastery of various study fields and social skills. Students are considered the main components in the learning process, with Law No. 20 of 2003 affirming their role as members of society developing their potential through formal education. The theoretical aspect discusses internal and external factors influencing students' social abilities, with the family as the first place for shaping social skills. Psychological factors, student conditions, interaction with the environment, and peer interactions are detailed in outlining factors affecting students' social development. The implications of these factors on students' academic achievement are also elucidated in the context of formal education. Emphasizing positive interactions among students and the impact of the community environment on students' learning outcomes becomes a crucial point in discussing the roles of schools and families in creating a supportive educational environment